Asset Supply Chain Management System-based IoT Technology for Higher Education Institutions - Kuandee, Watjanarat; Nilsook, Prachyanun; Wannapiroon, Panita (International Journal of Online and Biomedical Engineering (iJOE), 2019)
The purpose of this research is to design and develop an asset supply chain management system-based IoT technology for Higher Education Institutions (HEIs). Although nowadays there are computer-based asset information management systems, the problem is that such a system cannot immediately monitor the status of the asset. There is some information that is not related to reality, including a lack of asset movement records and information as to the status of each asset, which could lead to the mistake in terms of the working process which is unable to control and monitor a situation. Therefore, this re-search applied the concept of supply chain management (SCM) and IoT tech-nology in order to unsure good governance on the part of HEIs. This research is focused on durable articles and the use of a Near Field Communication (NFC) tag to communicate and exchange information with NFC-compatible smartphones. In this case, it can identify and monitor the asset under considera-tion and also assess associated information from any device. This solution can increase efficiency and value in terms of the organization. Moreover, the design diagram of the system leads to the development of asset supply chain manage-ment system (ASCMS)-based IoT technology for HEIs. The evaluation of the performance of this technology shows that the system operates at a great level, and that ASCMS-based IoT technology for HEIs it can be applied to ensure the good governance of such institutions. In addition, this research can serve the in-ternal organizational administration of Thai HEIs, involving dealing with working processes in line with real-life situations, relating to budget management, organizational working behaviors, and service users’ requirements. All of these aspects are analyzed based on good governance, including the rules of law, transparency and values.